Global Analysis of Dynamic Models in Economics and Finance Essays in Honour of Laura Gardini - Bischi, Gian Italo; Chiarella, Carl.; Sushko, Iryna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The essays in this special volume survey some of the most recent advances in the global analysis of dynamic models for economics, finance and the social sciences. They deal in particular with a range of topics from mathematical methods as well as numerous applications including recent developments on asset pricing, heterogeneous beliefs, global bifurcations in complementarity games, international subsidy games and issues in economic geography. A number of stochastic dynamic models are also analysed. The book is a collection of essays in honour of the 60th birthday of Laura Gardini.
Introduction -- Problems and Trends in Global Economic Dynamics (Including Specific Examples): Recent Developments on Asset Pricing with Heterogeneous Beliefs and Adaptive Behaviour of Financial Markets -- Modeling House Price Dynamics with Heterogeneous Speculators -- A Reconsideration of the Formal Minskyan Analysis -- Global Bifurcations in a Complementarity Game -- A Little Help from My Friend -- Pattern Formation in Economic Geography -- A Three-region New Economic Geography Model in Discrete Time -- Chaotic Dynamics in Organization Theory -- One-dimensional Discontinuous Piecewise-linear Maps and the Dynamics of Financial Markets -- Consistency of Linear Forecasts in a Nonlinear Stochastic Economy -- A Homoclinic Route to Volatility -- Mathematical Methods and Philosophy for Global Analysis of Dynamical Systems: Image Entropy for Discrete Dynamical Systems -- Embedding a Dim1 Piecewise Continuous and Linear Leonov Map into a Dim2 Invertible Map -- A Gallery of Bifurcation Scenarios in Piecewise Smooth 1D Maps -- Periodic Orbits and Their Bifurcations in 3D Maps with a Separate Third Iterate -- Complexities of Natural Selection Synamics.
Keywords: Economics; Functional equations; Finance; Economics -- Statistics; Economics, Mathematical; Economics/Management Science; Economic Theory; Difference and Functional Equations; Game Theory/Mathematical Methods; Quantitative Finance; Finance/Investment/Banking.; Statistics for Business/Economics/Mathematical Finance/Insurance.